Aktualna pitanja kaznenog zakonodavstva - 2007. - Mrčela, Marin; Benko, Marijan; Garačić, Ana; Goreta, Miroslav; Grgić, Melanija; Josipović, Ivo; Kaleb, Zorislav; Katušić-Jergović, Sanja; Kovačić, Antonija; Marijan, Ranko; Novosel, Dragan; Omejec, Jasna; et al. (2007)
Autor se u radu bavi aktualnim pitanjima kaznenog zakonodavstva i prakse.
Projekt MZOS
HRV